Dual-Band On-Body Repeater Antenna for In-on-On WBAN Applications - Jinpil Tak; Kyeol Kwon; Sunwoo Kim; Jaehoon Choi (International Journal of Antennas and Propagation)
A dual-band on-body repeater antenna for in-on-on wireless body area network applications is proposed. The proposed antenna has a maximum radiation normal to the human-body surface for communication with implanted devices in the 5.8 GHz industrial, scientific, and medical (ISM) band. In addition, to transmit the biological information received from the implanted devices to other on-body devices, the proposed antenna was designed to have a monopole-like radiation pattern along the surface of the human body for communication in the 2.45 GHz ISM band. The antenna was fabricated, and its performance was measured by attaching it to a human-equivalent semisolid phantom. In addition, the human-body effect was studied to ensure antenna performance under an actual situation.